A newly discovered Bordetella species carries a transcriptionally active CRISPR-Cas with a small Cas9 endonuclease - Ivanov, Yury V. (2015)
Background: Clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated genes (cas) are widely distributed among bacteria. These systems provide adaptive immunity against mobile genetic elements specified by the spacer sequences stored within the CRISPR. Methods: The CRISPR-Cas system has been identified using Basic Local Alignment Search Tool (BLAST) against other sequenced and annotated genomes and confirmed via CRISPRfinder program. Using Polymerase Chain Reactions (PCR) and Sanger DNA sequencing, we discovered CRISPRs in additional bacterial isolates of the same species of Bordetella. Transcriptional activity and processing of the CRISPR have been assessed via RT-PCR. Results: Here we describe a novel Type II-C CRISPR and its associated genes—cas1, cas2, and cas9—in several isolates of a newly discovered Bordetella species. The CRISPR-cas locus, which is absent in all other Bordetella species, has a significantly lower GC-content than the genome-wide average, suggesting acquisition of this locus via horizontal gene transfer from a currently unknown source. The CRISPR array is transcribed and processed into mature CRISPR RNAs (crRNA), some of which have homology to prophages found in closely related species B. hinzii. Conclusions: Expression of the CRISPR-Cas system and processing of crRNAs with perfect homology to prophages present in closely related species, but absent in that containing this CRISPR-Cas system, suggest it provides protection against phage predation. The 3,117-bp cas9 endonuclease gene from this novel CRISPR-Cas system is 990 bp smaller than that of Streptococcus pyogenes, the 4,017-bp allele currently used for genome editing, and which may make it a useful tool in various CRISPR-Cas technologies.